1969
DOI: 10.1029/jb074i027p06553
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse component of lunar radar echoes

Abstract: A simple model consisting of volume backscattering from within the lunar regolith can explain the observed diffuse component of lunar radar echoes. At a wavelength of 68 cm, a good match of the model with the data yields a value of 2.5–3 for the relative permittivity of the regolith in good agreement with the quasi‐specular backscattering estimates. The fit at 23 cm is poorer but yields a value slightly less than 2. At 3.8 cm, the value is below 1.5, and both that value and the 23 cm value are in good agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Hagfors [1967] pointed out that rocks were responsible for the diffuse scattering component, and that their nonspherical shape led to the observed partial polarization. Burns [1969] suggested that most of the scattering resulted from single scattering by rocks that were either on the lunar surface or buried in the regolith. Thompson et al [1970] modeled the single scattering behavior of rocks using Mie theory and suggested that models with single scattering by surface rocks or multiple scattering between buried rocks were capable of accounting for several observed properties of the diffuse component.…”
Section: Introductionmentioning
confidence: 99%
“…Hagfors [1967] pointed out that rocks were responsible for the diffuse scattering component, and that their nonspherical shape led to the observed partial polarization. Burns [1969] suggested that most of the scattering resulted from single scattering by rocks that were either on the lunar surface or buried in the regolith. Thompson et al [1970] modeled the single scattering behavior of rocks using Mie theory and suggested that models with single scattering by surface rocks or multiple scattering between buried rocks were capable of accounting for several observed properties of the diffuse component.…”
Section: Introductionmentioning
confidence: 99%
“…CT HV/ CT VV = 1/3) [39], [47], Such scattering features might correspond to rock edges, ground surface cracks, or other topographic discontinuities. The HV-polarized returns emerge as a second-order component in most theoretical treatments of scattering and are sometimes interpreted as solely arising from multiple scattering (e.g., [9]).…”
Section: B Empirical Models Based On Scale-dependent Roughness Parammentioning
confidence: 99%
“…Much of the early work in this field focused on the Moon, for which Surveyor panoramic photos provide ground-truth measurements of the surface rock population. Burns (1969) made one of the earliest efforts to relate radar backscatter to regolith subsurface properties. Thompson et al (Î970) and Pollack and Whitehill (1972) used a Mie scattering model for the regolith to determine the likely roles of surface and subsurface scattering in 70-cm radar echoes ;Campbell etal.…”
Section: Introductionmentioning
confidence: 99%